Evaluation of the hydration of Portland cement containing various carbonates by means of thermal analysis - Gabrovšek, Roman (Acta chimica slovenica, 2006)
Portland cement containing a fixed amount of mineral admixtures (calcium carbonate or dolomite or magnesite) was hydrated at 60 °C for 7- and 28 days. Phase compositions were evaluated by thermogravimetric analysis and by powder X-ray diffraction. Measurements of surface area indicated the development of the hydrated microstructure. Detailed analysis of DTG decomposition profiles of portlandite and carbonate enabled the evaluation of certain admixture-related parameters concerning portlandite formation and also indicated the behavior of specific carbonates during the hydration process.
Keywords: anorganska kemija; dodatki; hidratacija; karbonati; Portlandski cement; termična analiza